Potential vaccine hesitancy regarding COVID-19 vaccines in Kashmiri population - Syed Najmul Ain; Rabia Ahmad; Reyana Qulsum; Mohamad Azhar Gilani (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: India is all set to begin vaccination against COVID-19. A good number of people are falling prey to anti-vaccination campaigns, and therefore, some amount of vaccine hesitancy must have developed. The primary objective of the study was to find the level of potential COVID-19 vaccine hesitancy in Kashmiri population. MATERIALS AND METHODS: This was a cross-sectional study conducted in the valley of Kashmir. A predesigned questionnaire was shared online. The participation of respondents was voluntary. Exclusions were made on account of residence outside Kashmir valley, duplicate forms, and wrong information. The data were entered into Microsoft Excel 2010 and analyzed using SPSS version 23. RESULTS: A total of 487 respondents were included. About 67% of the participants were in the age group of ≤30 years, 55% female, 54% rural, and 16% had ever been COVID-19 positive. About 14% of the participants were completely hesitant about receiving the COVID-19 vaccine, whereas 40% were unsure if they will accept the vaccination. The main reason for the total nonacceptance of the vaccine was the doubts about the safety of COVID-19 vaccines (67%). Urban people were more likely to be hesitant to the vaccine than rural people (odds ratio [OR] 1.845, confidence interval CI 1.022 to 3.333). Those who were ever COVID-19 positive were 3.3 times more likely to say "no" to COVID-19 vaccination than those who were never positive. CONCLUSION: Strategic steps must be taken to minimize the vaccine hesitancy associated with COVID-19 vaccination. Authorities should direct efforts toward vaccine education, creating awareness among people about the importance of COVID-19 vaccination.